Effects of feeding Bacillus subtilis to heat stressed broiler chickens with or without an antibiotic growth promoter (Asian Journal of Medical and Biological Research, 2015)
The effects of feeding probiotic (PB) with or without Lincomycin 2.2% (AGP) were investigated in broiler chickens during summer. Seven hundred Cobb-500 one day old straight run broiler chicks were randomly distributed into four dietary treatments each of five replications. Four diets were compared: control; control diet plus PB (Bacillus subtilis DSM17299) at a level of 50g/100kg; control plus (AGP) at a level of 15g/100kg and control plus a combination of PB and AGP (50gm/100kg and 15g/100kg respectively). Control birds were fed on a corn-soybean based starter mash that contained ME 3000 kcal/kg and CP 24.39% from 0-21 days of age and a corn-soybean based grower mash of ME 3100 kcal/kg and CP 20.43% during 22-35 days of age. The records were kept of feed intake (FI), body weight and mortality while weight gain, feed conversion ratio (FCR) and survivability were calculated. Temperature and humidity were recorded four times daily except during extreme heat stress when measurements were made more frequently. One bird that was close to average of pen weight was taken from each replication at the end of the trial and the birds were sacrificed to determine carcass characteristics. Both performance and carcass yield data were statistically analyzed. Birds that received PB and a combination of PB +AGP treatments showed significant differences (P